Faktor Self-Acceptance Dan Interpersonal Skill Pada Individu Difabel Netra - Mumpuni, Sesya Dias; Florina, Ike Desi; Nurhayati, Sri Adi; Ekawati, Yulia Nur; Setia Rini, Eka Febry; Adinda, Choirunnisa (Jurnal Bimbingan dan Konseling Pandohop, 2023)
This study aims to investigate the relationship between self-acceptance factors and interpersonal skills in individuals with visual impairments in the context of daily life. The following is a summary of the findings and key findings. Self-Acceptance as a Key Foundation: Self-acceptance has been shown to be an important foundation in the development of interpersonal skills of individuals with visual impairments. Individuals who have high self-acceptance tend to have healthier and stronger interpersonal relationships. Influence of Internal and External Factors: Internal factors such as self-image, self-perception, and level of self-confidence play an important role in the self-acceptance of people with visual impairments. In addition, social support, inclusion in society, and accessibility also influence the level of self-acceptance. Better Interpersonal Skills: Individuals with visual impairments who have strong self-acceptance tend to have better interpersonal skills. They are better able to communicate clearly, understand others' feelings, and build healthy relationships. Implications for Quality of Life Improvement: The results of this study have important implications for improving the quality of life of individuals with visual impairments. Enhancing their self-acceptance through social support, empowerment, and accessibility can help in improving their interpersonal skills and creating a more fulfilling life.